Evidence for enhanced multi-component behaviour in Tourette syndrome - an EEG study - Brandt, Valerie C; Stock, Ann-Kathrin; Münchau, Alexander; Beste, Christian (Scientific reports, 2017)
Evidence suggests that Tourette syndrome is characterized by an increase in dopamine transmission and structural as well as functional changes in fronto-striatal circuits that might lead to enhanced multi-component behaviour integration. Behavioural and neurophysiological data regarding multi-component behaviour was collected from 15 patients with Tourette syndrome (mean age = 30.40 ± 11.10) and 15 healthy controls (27.07 ± 5.44), using the stop-change task. In this task, participants are asked to sometimes withhold responses to a Go stimulus (stop cue) and change hands to respond to an alternative Go stimulus (change cue). Different onset asynchronies between stop and change cues were implemented (0 and 300 ms) in order to vary task difficulty. Tourette patients responded more accurately than healthy controls when there was no delay between stop and change stimulus, while there was no difference in the 300 ms delay condition. This performance advantage was reflected in a smaller P3 event related potential. Enhanced multi-component behaviour in Tourette syndrome is likely based on an enhanced ability to integrate information from multiple sources and translate it into an appropriate response sequence. This may be a consequence of chronic tic control in these patients, or a known fronto-striatal networks hyperconnectivity in Tourette syndrome.
Keywords: Surveys and Questionnaires; Physical Stimulation; Humans; Neurophysiological Monitoring; Case-Control Studies; evokované potenciály; studie případů a kontrol; chování; Tourettův syndrom; mladý dospělý; dospělí; Female; lidé; elektroencefalografie; počítačové zpracování obrazu; Image Processing, Computer-Assisted; průzkumy a dotazníky; Adult; ženské pohlaví; fyzikální stimulace; Male; Evoked Potentials; Tourette Syndrome; Behavior; Young Adult; Electroencephalography; mužské pohlaví; neurofyziologický monitoring